NEWSPAPER READING BEHAVIOUR IN ACADEMIC LIBRARIES: A SURVEY OF TWO SATELLITE UNIVERSITY LIBRARIES IN GHANA - Owusu-Ansah, C. M.; Yebowaa, F. A.; Katsekpor, S. A. (UDS International Journal of Development, 2017)
The purpose of the study was to explore the newspaper reading behaviour of university students of the Kumasi campus of the University of Education Winneba (UEW-K) and the Wa campus of the University for Development Studies (UDS). The study made use of the survey design. A total questionnaire of 730 was self-administered to randomly selected students yielding an overall response rate of 558 (76.4%). Among others, the findings of the study showed that most students have a positive attitude to reading in the library; most students have a positive attitude to reading newspapers in the digital format; and most students believe reading newspapers can improve their current awareness of national issues and vocabulary. In respect of challenges, the study found inadequate copies of newspapers as the main challenge when students are reading newspapers in the library. Recommendations for academic libraries include adjusting newspaper collection development policies to include electronic newspaper subscriptions; conducting needs assessment to drive newspaper collection development; and setting up separate newspaper services unit with reading rooms. Keywords: Academic Libraries; Information Behaviour; Newspapers; Satellite CampusesÂ 